Effects of 36 hour fasting on GH/IGF-I axis and metabolic parameters in patients with simple obesity. Comparison with normal subjects and hypopituitary patients with severe GH deficiency - Maccario, M; Aimaretti, G; Grottoli, S; Gauna, C; Tassone, F; Corneli, G; Rossetto, R; Wu, Z; Strasburger, CJ; Ghigo, E (International Journal of Obesity, 2001)
Reduction of growth hormone (GH) secretion in obesity probably reflects neuroendocrine and metabolic abnormalities. Even short-term fasting stimulates GH secretion and distinguishes normal from hypopituitary subjects with growth hormone deficiency (GHD). Marked weight loss improves GH secretion in obesity but the effect of fasting is controversial. We studied the effects of a 36 h fasting on the GH/IGF-I axis and metabolic parameters in obesity. We studied nine obese patients (OB; three male and six female; age, 29.2+/-4.8; range, 18-59 y; body mass index (BMI), 43.4+/-2.7 kg/m(2); WHR, 0.9+/-0.1). Fifteen normal subjects (NS; eight male and seven female 28.9+/-0.6, 25-35 y; 21.6+/-0.4 kg/m(2)) and 10 adult hypopituitary patients with severe GH deficiency (GHD; seven male and three female; 37.6+/-2.3, 29-50 y; 24.5+/-1.0 kg/m(2); GH peak<3 microg/l after ITT and/or<9 microg/l after GHRH+arginine) served as control groups. We studied the effects of 36 h fasting on 8 h diurnal mean GH, insulin and glucose concentrations (mGHc, mINSc and mGLUc; assay every 30 min from 8.00 am to 4.00 pm) as well as on IGF-I, IGFBP-3, ALS, IGFBP-1, GHBP and free fatty acid (FFA) levels. Before fasting, basal IGF-I and ALS levels in OB were similar to those in NS and both were higher (P<0.001) than those in GHD. IGFBP-3 levels in OB were lower (P<0.01) than in NS but higher (P<0.02) than in GHD. GHBP levels in OB and GHD were similar and both were higher (P<0.01) than in NS. Glucose levels were similar in all groups. FFA levels in OB were higher (P<0.01) than in NS but similar to those in GHD. IGFBP-1 in OB were lower (P<0.05) than in NS and GHD which, in turn, were similar. On the other hand, mINSc in OB was higher (P<0.01) than that in NS and GHD which, in turn, were similar. The mGHc in OB was similar to that in NS but only the latter was higher (P<0.05) than in GHD. The individual mGHc in the three groups overlapped. After fasting, IGF-I levels in GHD were unchanged while they decreased in OB (P=NS) as well as in NS (P<0.01). IGFBP-3 and ALS levels did not change. GHBP levels in OB and GHD were unchanged while they increased in NS (P<0.01). Glucose and FFA levels were reduced and increased, respectively, in all groups (P<0.02 and P<0.01). IGFBP-1 increased while mINSc decreased in all groups (P<0.02 and P<0.01); in OB they persisted lower and higher (P<0.01) respectively, than in NS and GHD. Fasting significantly increased mGHc in NS (P<0.001) but not in OB as well as in GHD. Individual mGHc in OB showed persistent overlap with GHD. Short-term fasting does not increase GH secretion in obesity and does not distinguish somatotroph function in obese from that in severe GHD adults. Short-term fasting in obesity has attenuated effects on insulin and IGFBP-1 secretion while it normally increases free fatty acids in spite of any change in GH secretion.